A case of afferent loop obstruction caused by internal hernia incarcerated into the mesenteric gap between the efferent and afferent loops after billroth II gastrectomy - FUKUDA, Toshikatsu; TAGUCHI, Kazuhiro; NAKAHARA, Masahiro; TAKAHASHI, Gen; HAMAOKA, Michinori; SUMITANI, Daisuke (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2012)
We report an extremely rare case of afferent loop obstruction after distal gastrectomy. A 76-year-old man was admitted to our hospital with vomiting and abdominal pain. He had undergone distal gastrectomy combined with Billroth II reconstruction added-Braun anastomosis for gastric cancer about 50 days ago. Abdominal computed tomography scan revealed severe dilatation of the afferent loop. Therefore, we diagnosed afferent loop obstruction and performed emergency surgery. Emergency surgery showed the afferent loop and the duodenum to be dilated. The small intestine was observed to fit into the mesenteric gap between the efferent and afferent loops. The mesenteric gap took the form of an internal hernia. The afferent loop was obstructed by an adhesive band between the mesentery of the afferent loop and that of the incarcerated small intestine. We cut the band and repositioned the incarcerated small intestine. No bowel resection was required. The hernial orifice formed as a result of the mesenteric gap was closed by suturing.